Fisherian and Ricardian trade - Stefan Sinn (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1991)
This paper discusses the difference between Fisherian and Ricardian trade in terms of a simple two-period model of a small open economy. Fisherian or intertemporal trade occurs when goods are traded today against the promise to deliver goods in the future. The resulting net resource transfer is equal to an international flow of capital. Ricardian trade occurs when there are no international capital flows and the trade account is balanced. The model suggests that once international trade is primarily of Fisherian nature, the direction and volume of trade are best explained by variables that take intertemporal aspects into consideration such as the interest rate and the expected prices of goods.
Keywords: F21; F32; F41; 330; International capital mobility; saving; investment; current account adjustment; Kapitalmobilität; Sparquote; Gesamtwirtschaftliche Investitionstheorie; Leistungsbilanz; Offene Volkswirtschaft; Theorie